Growth, Nodulation, Yield and Nutrient Uptake of Urdbean (Vigna mungo L. Hepper) as Influenced by Sulphur and Iron Fertilization in Light Textured Soil - Singh, Onkar; Kumar, Satendra; Shahi, U. P.; Kumar, Ashok; Dwivedi, Ashish; Kumar, Vineet (International Journal of Bio-resource and Stress Management, 2023)
In recent days, continuous rotation of cereals like rice-wheat without judicious use of chemical fertilizer put agricultural sustainability and environmental safety under trouble. Keeping these aspects on minda thrice replicated field trial conducted on sandy loam soil of S.V.P.U.A. & T. Meerut (Uttar Pradesh) in kharif season 2013. Nine treatments viz.,T1 [Control (RDF-20:40:0)], T2 (RDF+Sulphur 20 kg ha-1 ), T3 (RDF+Sulphur 40 kg ha-1), T4 (RDF+Fe 2.5 kg ha-1 ), T5 (RDF+Fe 5 kg ha-1), T6 (RDF+Sulphur 20+Fe 2.5 kg ha-1), T7 (RDF+Sulphur 20+Fe 5.0 kg ha-1), T8 (RDF+Sulphur 40+Fe 2.5 kg ha-1) and T9 (RDF+Sulphur 40+Fe 5.0 kg ha-1) were tested in RBD with three replications by using F test. The data on growth, nodulation and yield with its attributing trait were recorded on net plot area basis. (18 m2), moreover, nutrient uptake was calculated as per the standard procedure. The results revealed that plant height (51.57 cm), number of branch plant-1 (22.94), dry weight (12.10 g plant-1) number of nodules plant-1 at 30 DAS (54.39), biological yield (25.68) and nutrient uptake in straw were significantly maximum by the application of RDF along with Sulphur 40 kg ha-1 and Fe 5.0 kg ha-1 while test weight (44.60 g), harvest index (42.33%) and nutrient uptake in grain was more with under RDF along with Sulphur 40 kg ha-1 and Fe 2.5 kg ha-1. However, Biological yield was positively related to all growth parameters. As its legume in nature, so it is highly eco-friendly and useful for sustainable agriculture besides maintain health of soil.